Fatigue crack growth rate analysis in an api 5l x70 steel pipe - Sorrija, Bruno A [UNESP]; Nascimento, Marcelino P [UNESP] (My University, 2015)
In this work a study of the fatigue crack growth rates in specimens taken from 90o and 180o of a welded joint of an API 5L X70 steel pipe, which is used in the manufacture of oil and gas pipelines, has been made. This class of steel show high strength and ductility values, and has been increasingly studied due the growing demand of oil and natural gas, which in consequence, increases the needing of new pipelines to transport them. The material studied has been directly taken from a tube provided by Tenaris Confab, according to the standards API 5L and ASTM E647, for the tensile tests and fatigue crack growth respectively. The results of the tensile tests obtained are in accordance with the specifications of the API 5L. The results of the fatigue crack growth rate tests showed significant differences between regions situated 90° and 180° of the welded joint region, which can be potentially related to the steel pipe manufacturing process. Metallographic and microhardness analysis of the base material and welded joint complemented this work.